Individual and group-level optimization of electric field in deep brain region during multichannel transcranial electrical stimulation - Nishimoto, Hidetaka; Kodera, Sachiko; Otsuru, Naofumi; Hirata, Akimasa (Frontiers in Neuroscience, 2024)
Electrode montage optimization for transcranial electric stimulation (tES) is a challenging topic for targeting a specific brain region; targeting the deep brain region is difficult due to tissue inhomogeneity, resulting in complex current flow. In this study, a simplified protocol for montage optimization is proposed for multichannel tES. Analysis of the electric field (EF) has been conducted using volume conductor model with in individual anatomical head models. The optimization procedure is simplified using the surface EF of the deep brain target region considering its small volume and nonconcentric distribution of the electrodes. Our proposal aimed to reduce the computational cost by >90%. A total of 6-8 electrodes were necessary for robust EF in the target region, depending on the region. The optimization with surface EF is comparable to or marginally better than using conventional volumetric EF for deep brain tissues. Electrode montage with mean injection current amplitude derived from individual analysis was demonstrated to be useful for targeting the deep region at the group level. The optimized montage and injection current were derived at the population level. Our proposal at individual and group levels showed great potential in clinical application.